Współczesne narzędzia komunikacji w placówkach oświatowych - Żebrok, Przemysław (Kultura-Społeczeństwo-Edukacja, 2019)
The subject of the paper deals with the issues of communication in educational institutions. Effective exchange of information plays a key role in achieving the desired results in every organization. This depends largely on the tools, language and the way the content is delivered. In the modern world communication is increasingly carried out by means of digital communication. Examples include e-registers, organizational sheets, electronic mail and websites, which have become the main tools for communicating information in educational institutions.